Pharmacognostical Studies on Three Asplenium Species - M. Johnson*, V. Irudayaraj and (Journal of Phytology, 2011)
The present study was aimed to study the pharmacongonstical characters viz., morphological and physico-chemical characteristics of three rare medicinally important spleenworts viz. Asplenium affine Swartz, Asplenium decrescens Kunze and Asplenium zenkeranum Kunze. The present study revealed the presence of alkaloids, triterpenes, and flavonoids in Asplenium species. Based on the Thin Layer chromatogram, interspecific relationship was assessed. A. affine and A. decrescens showed 42% of similarity coefficient and A. zenkeranum was varied from A. affine and A. decrescens with 36% variance.